0143 Associations Between Slow Wave Sleep Duration, Insulin Resistance, and Respiratory Effort-Related Arousals in Young Adults. (27th April 2018) - Rivas, J; Sharma, R; Miller, M D; Godinho, A; Ayappa, I; Jean-Louis, G; Varga, A W; Convit, A; Osorio, R S
Abstract: Introduction: Sleep duration has decreased significantly in the US over the past 50 years. Short sleep duration and sleep disruption have been associated with obesity, insulin resistance (IR) and increased risk of type 2 diabetes (T2DM). When examining the sleep patterns of obese young adults, obstructive sleep apnea (OSA) with severe blood oxygen desaturation is rare, while respiratory effort-related arousals (RERAs) resulting in sleep disruption are common. However, it is still unclear as to how the presence of RERAs in young adults plays a role in IR. Thus, we hypothesized that RERAs would be associated with decreased slow wave sleep (SWS) duration and higher IR and mediate the association between short SWS and IR. Methods: 21 cognitively normal subjects (age 20 ± 1.4, BMI 34 ± 5.9) completed one night nocturnal polysomnography (NPSG). Apneas were defined as absence of airflow for ≥10''. Hypopnea (3% or arousal) were defined as a reduction in the amplitude of breathing by 30% or more for ≥10'' accompanied by ≥3% decline in blood O2Sat or an arousal. Standard QUICKI scores were generated using fasting insulin and glucose. Pearson correlations were performed to study the associations between QUICKI, SWS duration and RERAs (measured as AHI3a). Results: A significant association was found between QUICKI and SWS [r=0.44, p=.046]. There was a significant relationship between SWS and RERAs [r=-0.46, p=0.034]. However, we found no association between QUICKI and RERAs (and therefore no mediation effects). Conclusion: Our findings suggest a relationship between increased IR and decreased SWS in the young obese. The presence of RERAs had an effect on the duration of SWS, which could be relevant for glucose control, school performance, and quality of life. We weren't able to show the effects of SWS on IR were mediated by RERAs. One of the limitations was the small sample size and cross-sectional design, which limits the understanding of the directionality of these associations. Future studies on metabolic disorders and sleep are required to better understand the physiological effects of IR on sleep in younger populations. Support (If Any):